2018
DOI: 10.1016/j.jpainsymman.2017.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Use of Intensive and Supportive Procedures for Patients With Stroke in Taiwan in the Last Month of Life Between 2000 and 2010

Abstract: Context. Stroke is the second leading cause of death and the primary cause of disability worldwide. It is uncertain what care patients with stroke receive in their end of life and what trends in care are in recent years. Objectives. The objective of this study was to investigate the changes in the use of intensive and supportive procedures for Taiwanese patients with stroke in their last month of life during 2000e2010. Methods. Analysis of claims data of 55,930 patients with stroke obtained from the National H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In 2015, the Taiwanese legislature passed the Patient Right to Autonomy Act, which is the first law in Asia aimed at protecting a patient's right to autonomy, including exercising the right to refuse medical treatments through ADs [28]. After the passing of the Hospice Palliative Care Act, Taiwan experienced an increase in supportive care use in different intensive care units for stroke patients and a decline in the use of intensive procedures [29]. In addition, population-based studies have found that the implementation of palliative care policies in Taiwan was associated with improved palliative care utilization in connection with cancer, dementia, chronic obstructive pulmonary disease, and stroke [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, the Taiwanese legislature passed the Patient Right to Autonomy Act, which is the first law in Asia aimed at protecting a patient's right to autonomy, including exercising the right to refuse medical treatments through ADs [28]. After the passing of the Hospice Palliative Care Act, Taiwan experienced an increase in supportive care use in different intensive care units for stroke patients and a decline in the use of intensive procedures [29]. In addition, population-based studies have found that the implementation of palliative care policies in Taiwan was associated with improved palliative care utilization in connection with cancer, dementia, chronic obstructive pulmonary disease, and stroke [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…After the passing of the Hospice Palliative Care Act, Taiwan experienced an increase in supportive care use in different intensive care units for stroke patients and a decline in the use of intensive procedures [29]. In addition, population-based studies have found that the implementation of palliative care policies in Taiwan was associated with improved palliative care utilization in connection with cancer, dementia, chronic obstructive pulmonary disease, and stroke [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Each multivariate logistic regression model was adjusted for age, sex, insurance premium level, urbanization level of the hospital location, accreditation level of the hospital, ownership of the hospital, and Charlson Comorbidity Index, and these confounders have been described as determinants of these invasive procedures in previous studies. 6,27,28 The results of multivariate analysis were stratified by disease type. Stratum 1 comprised the COPD decedents, and stratum 2 comprised the LC decedents.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Patient Right to Autonomy Act was passed by the Taiwanese legislature in 2015 and it was the first law in Asia to protect a patient’s right to autonomy including exercising the right to refuse medical treatments through ADs [ 47 ]. Several population-based studies revealed that the implementation of palliative care policies, namely the Patient Right to Autonomy Act in Taiwan was associated with improved palliative care utilization in regards to cancer and non-cancer diseases such as chronic obstructive pulmonary disease, dementia, and stroke [ 48 50 ]. This underscores the benefits of having ADs and therefore the importance of exploring the influential predictors of signing ADs in terminally ill patients.…”
Section: Discussionmentioning
confidence: 99%